2005
DOI: 10.2337/diacare.28.9.2141
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Is Associated With Dramatically Decreased Survival in Female but Not Male Subjects With Cystic Fibrosis

Abstract: OBJECTIVE—Survival analysis was performed on a prospectively followed cohort of patients with cystic fibrosis (CF) to determine the impact of the development of diabetes on survival. RESEARCH DESIGN AND METHODS—Clinical data were retrieved for patients diagnosed with CF-related diabetes (CFRD) at the Minnesota CF Center in 1987–2002. Kaplan-Meier survival analysis was performed to estimate median survival. Data were analyzed by Cox regression to evaluate the influence of clinical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
168
4
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(179 citation statements)
references
References 30 publications
5
168
4
2
Order By: Relevance
“…An association between poor pulmonary function and CFRD has been reported from cross-sectional studies (4 -6), and other studies have demonstrated accelerated decline in pulmonary function before diagnosis of CFRD (2,25). In cystic fibrosis, it is possible that prediabetic (or prediagnostic) states worsen pulmonary function.…”
Section: Risk Factorsmentioning
confidence: 96%
“…An association between poor pulmonary function and CFRD has been reported from cross-sectional studies (4 -6), and other studies have demonstrated accelerated decline in pulmonary function before diagnosis of CFRD (2,25). In cystic fibrosis, it is possible that prediabetic (or prediagnostic) states worsen pulmonary function.…”
Section: Risk Factorsmentioning
confidence: 96%
“…It is not clear whether or not these two facts are connected. Milla et al 57 found that the median age of survival was 30.7 years for females with CFRD, and for males it was 47.4 years. It must be noted that this difference in age survival may be due to CFRD or it may arise from other factors (e.g.…”
Section: Prognosismentioning
confidence: 99%
“…CFRD has a burden of complications, chiefly the deterioration of pulmonary function (7)(8)(9), but also classic diabetes complications, as recently shown (10,11). Overall, CFRD increases the mortality risk, particularly in females (12).…”
Section: Introductionmentioning
confidence: 99%